In Silico Prediction and Characterization of MicroRNAs from Aphis gossypii (Hemiptera: Aphididae). (1st March 2014) - Rebijith, K B; Asokan, R; Krishna, V; Hande, Ranjitha H; Kumar, N K Krishna; Ramamurthy, V V
Abstract: MicroRNAs (miRNAs) are small noncoding RNAs that regulate gene expression either bymRNAcleavage or by translational repression. They play an important role in the development and physiology of organisms. It is difficult to experimentally identify miRNAs and characterize their spatial and temporal expressions in insects or in any organisms. The cotton or melon aphid, Aphis gossypii Glover, is an important pest. It is a major vector of many plant viruses that often cause crop failures. Developing futuristic management approaches exploiting small RNAs like miRNAs may provide options for effective management of this pest species. To achieve this goal, identification and characterization of miRNAs from A. gossypii is a prerequisite. In this study, we used computational approaches, primarily depending on similarity search and secondary structure prediction, to identify 16 potential miRNAs from 88, 851 A. gossypii expressed sequence tag sequences. Phylogenetic analyses showed A. gossypii mature miRNAs are highly conserved with respect to other members in the animal kingdom. Functional annotation of the newly predicted miRNAs revealed that the majority of them are involved in the regulation of transcription and signal transduction. With further experimental verification, miRNAs predicted in this study may provide valuable tools for insect pest management in the future.